Public value of e-Government investments in the developing countries: empirical exploration of the public sector in Kenya - Okong'o, Kennedy Odiwuor (Department of Information Systems, 2017)
In private and public sectors, Information Communication Technologies (ICTs) have become a phenomenal asset of resource in strategic management. In developed countries, ICTs are critical tools in the public sector strategy. In specific, Electronic Government has been identified as one of the major competencies required to re-invigorate governance, enhance performance and reduce red-tape bureaucracies in the public sector, e-Government being the use of ICTs in the transformation of public organizations towards efficient service delivery. Though information systems as a discipline has offered some research outputs on the value and the effects of ICTs in the private sector, similar focus on the public sector or e-Government is relatively thin. While the few existing researches have had a relatively weightier focus on developed countries, the evidence-based empirical studies in information systems that have focused on developing countries have produced contradictory results, hence the need for further research to attempt a re-alignment in this sub domain of e-Government. Therefore, this pursuit departs from most past researches by delving into the effects of e- Government investments using theoretical lenses drawn upon disciplines that are outside the mainstream information systems domain. These include public administration, political sciences and public economics. Using a mixed methods approach, a balanced panel data of Kenya's key ministries for a 10-year period of 2004 to 2014 following the launch of e-Government strategy of 2004, audited national government ministries' expenditures, census data, e-Government spending, consumer price indices, gross domestic products, parameters on governance and other data on public services, this research sought to examine the nature and dimensions of public values that the developing countries derive as a consequence of investment in e-Government.